Gap in Watershed Project Activities: A Study at Micro Level - R.K.Raj,; C.Satpathy,; Shyamlal, (Journal of Agricultural Extension Management, 2025)
The national Watershed Development Programme was launched in India during 1995. Ministry of Rural Development, Govt. of lndia has formulated guidelines and circulated to all concerned for effective implementation of the programme. The guideline emphasized up gradation and adoption of low cost technologies and materials for sustainable development, capacity building of the people through training and exposure as well as development of entrepreneurial skills. The watershed association will relieve funds from DRDA and utilize as per the action plan formulated. So, the programme is people oriented programme and the guideline provides sufficient operational flexibility at different levels enabling to respond to different situations and aspirations of the watershed communities. Attempt was therefore made to make a study to assess the gap in watershed development project activities